Нанокомпозиты на основе опаловых матриц с 3D-структурой, образованной магнитными наночастицами - Rinkevich, A. B.; Ustinov, V. V.; Samoilovich, M. I.; Belyanin, A. F.; Klescheva, S. M.; Kuznetsov, E. A. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
The interaction of electromagnetic waves with nanocomposite materials obtained by introducing nickel–zinc or manganese–zinc ferrite nanoparticles into the interspherical space of opal matrices (regular packings of SiO₂ nanospheres with a diameter of about 250 nm) has been studied. Measurements were carried out in the frequency range of 26–38 GHz in magnetic fields with intensities up to 30 kOe. It was established that the main cause of the microwave variations is magnetic resonance in the nanocomposite.